PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR IPS SISWA KELAS V (PIONIR: JURNAL PENDIDIKAN, 2022)
The learning process at SDN Mangun Jaya 01 has not implemented an interactive learning model for students because during the learning process it still uses monotonous and conventional learning, resulting in low learning outcomes. The purpose of this study was to determine the effect of the cooperative learning model type Student Teams Achievement Division (STAD) on the learning outcomes of social studies students of class V. In this study, the approach used by the researcher was experimental quantitative and the research method used was True Experimental and the design used was Post-test Only Control Group Design. Sampling using saturated samples using classes VA and VB, then the entire population in classes VA and VB will be used as research samples. The instrument in this study was a multiple choice test sheet. Analysis of learning outcomes using t test. Based on the results of the analysis obtained  >  = 2,699 > 2000 so that is accepted and is rejected. So it can be concluded that there is an effect of the Cooperative Learning learning model Type Student Teams Achievement Divisions (STAD) on Social Studies Learning Outcomes for Class V students.